Is it inside my head? Characterization of sound externalization in schizophrenia - Laure Fivel; Mathieu Lavandier; Nicolas Grimault; Fabien Perrin; Marine Mondino; Frédéric Haesebaert (PLoS ONE, 2026)
Schizophrenia has been linked to reality monitoring confusions, particularly misattributions of internal productions to external sources. We hypothesized that these misattributions may be related to deficits in processing acoustic cues that distinguish the subjective experience of a sound source inside or outside the head, i.e., sound externalization. This study aimed to investigate sound externalization in patients with schizophrenia, particularly for emotional sounds, as emotion influences auditory perception. In an externalization task, twenty-three patients with schizophrenia and twenty-five healthy controls were exposed to neutral and emotional sounds processed to be perceived as: internalized (diotic) or externalized (filtered with either an anechoic head-related transfer function -HRTF- or a binaural room impulse response -BRIR). Participants had to indicate whether the sound source was perceived inside or outside their head. Exploratory analyses also examined the relationships between externalization, reality monitoring, and symptom severity. Compared to controls, patients with schizophrenia rated the filtered sounds (HRTF, BRIR) as less externalized (corrected p < .001) and the diotic sounds as more externalized (corrected p < 0.001). Sounds with negative emotional (anger, fear) were more externalized (corrected p < .001) in both groups, but patients showed reduced externalization when compared to control for several emotions (anger, happiness, fear, sadness) (corrected p < .001). No significant correlation was found between externalization and reality monitoring. In patients, greater symptom severity was associated with reduced externalization of sounds simulated as originating outside the head. These findings suggest an abnormal perception of sound sources in patients with schizophrenia, who confuse sounds inside and outside the head to a greater extent with an influence of emotional contents. Further research is needed to elucidate the relationship between sound externalization and symptoms such as hallucinations.